Review articleBrachytherapy in breast cancer - Fijuth, Jacek (Journal of Contemporary Brachytherapy, 2009)
Breast conserving surgery (BCS) with postoperative radiotherapy has been a standard treatment of early stage breast cancer for the last 30 years. Interstitial brachytherapy has been used as a boost therapy after whole breast external beam radiotherapy (EBRT), and recently, it’s been investigated in selected patients as a possible technique of a single radiotherapy modality (partial breast irradiation, PBI) after tumorectomy. Further clinical studies are required to define the most appropriate candidates for breast brachytherapy as a sole modality treatment and to determine the best delivery method of brachytherapy (multicatheter interstitial implant vs. balloon brachytherapy) in such patients.